2004
DOI: 10.1186/1472-6963-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Audit of head injury management in Accident and Emergency at two hospitals: implications for NICE CT guidelines

Abstract: Background: The National Institute for Clinical Excellence (NICE) has produced guidelines on the early management of head injury. This study audits the process of the management of patients with head injury presenting at Accident and Emergency (A&E) departments and examines the impact upon resources of introducing NICE guidelines for eligibility of a CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It is noteworthy that CT head scans performed for head injuries from the A&E went up in this period when the change in practice of handling calls for out-of-hours imaging was implemented and almost half of the scans requested were for head injuries. Although the trend of increase in A&E head injury CT scans with the advent of NICE guidelines is consistent with other published studies [ 1 - 5 ], the results fall short of statistical significance. This was probably because the lack of study power, which was one of the limitations of our study.…”
Section: Discussionsupporting
confidence: 78%
“…It is noteworthy that CT head scans performed for head injuries from the A&E went up in this period when the change in practice of handling calls for out-of-hours imaging was implemented and almost half of the scans requested were for head injuries. Although the trend of increase in A&E head injury CT scans with the advent of NICE guidelines is consistent with other published studies [ 1 - 5 ], the results fall short of statistical significance. This was probably because the lack of study power, which was one of the limitations of our study.…”
Section: Discussionsupporting
confidence: 78%
“…28,31,34,40,41 This is also true of other trauma caused by various mechanisms such as falls and motor vehicle crashes, where most of the patients are males. 28,34 Although our study population depicted that the predominant race is mainly African American, this is not typical of findings in other similar studies 28,31,40,41 ; this variation is likely due to the patient demographics of the surrounding community served by CHW. Our findings show that the level of agreement between the P and ED GCS scores was good.…”
Section: Discussionmentioning
confidence: 95%
“…It was discovered that undiagnosed intracranial hematomas often have tragic consequences in apparently mild TBI patients 35 and that CT scans reveal intracranial lesions in this population more commonly than expected. 36 Although there were pleas for more liberal use of CT scans in mild TBI, 37,38 several authorities suggested that this would be too costly, [39][40][41][42] and the concern persists to this day. 43 Studies have confirmed that a liberal policy of CT scans for mild TBI can be delivered cost-effectively.…”
Section: Neurosurgical Clinical Prediction and Decision Rulesmentioning
confidence: 99%